Perspective: Photonic flatbands - Leykam, Daniel; Flach, Sergej (APL photonics, 2018)
Flatbands are receiving increasing theoretical and experimental attention in the field of photonics, in particular in the field of photonic lattices. Flatband photonic lattices consist of arrays of coupled waveguides or resonators where the peculiar lattice geometry results in at least one completely flat or dispersionless band in its photonic band structure. Although bearing a strong resemblance to structural slow light, this independent research direction is instead inspired by analogies with “frustrated” condensed matter systems. In this Perspective, we critically analyze the research carried out to date, discuss how this exotic physics may lead to novel photonic device applications, and chart promising future directions in theory and experiment.